1999
DOI: 10.1073/pnas.96.17.9879
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: A new mechanism of neurodegeneration: A proinflammatory cytokine inhibits receptor signaling by a survival peptide

Abstract: Heightened expression of both a proinflammatory cytokine, tumor necrosis factor α (TNF-α), and a survival peptide, insulin-like growth factor I (IGF-I), occurs in diverse diseases of the central nervous system, including Alzheimer’s disease, multiple sclerosis, the AIDS-dementia complex, and cerebral ischemia. Conventional roles for these two proteins are neuroprotection by IGF-I and neurotoxicity by TNF-α. Although the mechanisms of action for IGF-I and TNF-α in the central nervous system originally were esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
119
0
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(125 citation statements)
references
References 62 publications
5
119
0
1
Order By: Relevance
“…In neurons the wide-ranging nature of regulation at the level of the docking proteins, such as IRS-1, is indicated by the observation that interference at the docking site is not restricted to the effect of IL-1β on neurotrophin signaling in cerebral cortical cells. In an earlier study Venters et al [72] have shown that another proinflammatory cytokine, TNFα interferes with signaling of a member of another trophic factor IGF-1 at the level of IRS-2 in cerebellar granule cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In neurons the wide-ranging nature of regulation at the level of the docking proteins, such as IRS-1, is indicated by the observation that interference at the docking site is not restricted to the effect of IL-1β on neurotrophin signaling in cerebral cortical cells. In an earlier study Venters et al [72] have shown that another proinflammatory cytokine, TNFα interferes with signaling of a member of another trophic factor IGF-1 at the level of IRS-2 in cerebellar granule cells.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism involves a suppression of the activation of the docking proteins [81]. It has also been shown that the IGF-1-promoted survival of cerebellar granule cells is compromised by the proinflammmatory cytokine TNFα by suppressing the activation of the docking protein IGF-2 [72]. Thus like insulin resistance in peripheral tissues and a similar resistance to IGF-1 in cerebellar neurons there may be a mechanism of resistance to neurotrophins in the brain, predisposing neurons to dysfunction and placing them at increased risk for functional defects and degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Although TNF is unable to induce apoptosis in these cells alone, it is capable of reversing IGF-1 prevention of apoptosis. 277,278 The mechanism for this appears to be via inhibition of IGF-1-receptor-induced phosphorylation of IRS-2 and the subsequent inability of this to activate PI3-kinase. 277,278 These results suggests that with regards to signaling pathways that lead to apoptosis; that inhibition of kinases or activation of phosphatases which signal cell survival may be an important mechanism used by apoptosis inducing signaling pathways.…”
Section: Cross Talk Between Apoptotic and Anti-apoptotic Signaling Pamentioning
confidence: 99%
“…Apoptosis may also occur via the ability of some receptors to inhibit signaling by other receptors that are thought to have a role in prevention of apoptosis. 277,278 These investigators have found using cerebral granular neurons that IGF-1 prevents apoptosis of these cells cultured in low K+ medium. Although TNF is unable to induce apoptosis in these cells alone, it is capable of reversing IGF-1 prevention of apoptosis.…”
Section: Cross Talk Between Apoptotic and Anti-apoptotic Signaling Pamentioning
confidence: 99%
“…Many of the agents that induce serine/threonine phosphorylation of IRS-1 also activate JNK, including TNF␣, interleukin-1␣, hyperglycemia, and insulin itself (14, 28, 34, 64 -67). Although the phosphorylation of Ser 307 as a general mechanism to inhibit IRS-1 function is not understood, it might provide a framework to understand the inhibition of insulin or IGF-1 signaling by proinflammatory cytokines under a variety of physiological conditions (23,24,28,29,34,68,69).…”
Section: Ser 307 Is Critical For the Inhibition Of Insulin-stimulatedmentioning
confidence: 99%